Queer Identities - Drushel, Bruce E. (Cambridge Scholars Pub., 2009)
Queer Identities/Political Realities examines the intersection of political leadership, media coverage, and sexual identity with particular emphasis on the negotiation of meaning between public behavior and private behavior in the United States. Centering on cases that illuminate key issues, each chapter questions assumptions about media coverage and extends current theoretical understanding. Each chapter focuses on a specific case within the broader conceptual fabric of queer theory, media ...